Controlling the cure time of geopolymer compositions containing high CA reactive aluminosilicate materials

By incorporating a retardant, such as barium chloride, into geopolymer compositions made from reactive high-Ca aluminosilicate salts, the curing time can be controlled, addressing the rapid curing issue and enabling more practical and cost-effective application in construction.

JP7650524B2Active Publication Date: 2025-03-25CATHOLIC UNIV OF AMERICA
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023010132
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-08-22
Filing Date
2023-01-26
Publication Date
2025-03-25
Estimated Expiration
2038-11-16

AI Technical Summary

Technical Problem

Geopolymer compositions made from reactive high-Ca aluminosilicate salts cure and harden too quickly, posing challenges for engineering applications that require longer curing times to allow for transport and placement. Additionally, extending curing times beyond what is economically viable is undesirable.

Method used

A geopolymer composition with a controllable cure time is achieved by combining at least one reactive aluminosilicate, at least one retardant, and at least one alkali silicate active agent solution. The use of metal salts, such as barium chloride, dissolved in water and mixed with the alkali silicate solution, helps control the release of silicate species, thereby extending the curing time.

Benefits of technology

The proposed solution effectively prolongs the curing time of geopolymer compositions, allowing for more manageable and economical construction processes while maintaining the strength and durability required for construction materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007650524000007
    Figure 0007650524000007
  • Figure 0007650524000008
    Figure 0007650524000008
  • Figure 0007650524000001
    Figure 0007650524000001
Patent Text Reader

Abstract

The use of a set retarder improves proper control of set time. The present disclosure provides a geopolymer composition with controllable set time that includes at least one reactive aluminosilicate, at least one retarder, and at least one alkali silicate activator solution.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The disclosed invention relates generally to admixtures for geopolymer compositions. More specifically, the invention relates to geopolymer compositions that can be used for specific applications and retarding admixtures for effectively controlling hardening in geopolymer systems. [Background technology]

[0002] In general, geopolymers made with certain reactive high-Ca aluminosilicates will set and harden very quickly due to the rapid formation of calcium silicate hydrate and calcium aluminosilicate hydrate gels. In engineering practice, the setting time of geopolymers should be fairly long. This means that concrete or mortar made with pozzolanic binders will require a long enough setting time to allow for transportation and placement. Summary of the Invention [Problem to be solved by the invention]

[0003] However, too long a curing time is uneconomical, i.e., improving proper control of curing time by using curing retarders is important for successful application of geopolymer materials in the construction and building industry. [Means for solving the problem]

[0004] (Summary of the invention) According to a first broad embodiment, the present disclosure provides a geopolymer composition having a controllable cure time that includes at least one reactive aluminosilicate, at least one retarder, and at least one alkali silicate activator solution. According to a second broad embodiment, the present disclosure provides a method for producing a geopolymer composition having a controllable cure time, comprising combining at least one reactive aluminosilicate, at least one retarder, and at least one alkali silicate activator solution.

[0005] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate exemplary embodiments of the invention and, together with the general description above and the detailed description below, serve to explain features of the invention. [Brief description of the drawings]

[0006] [Figure 1] 1 shows Raman spectra of sodium silicate activator solutions containing 0%-5% barium chloride monohydrate BWOB according to one embodiment of the present disclosure.

[0007] [Diagram 2] 1 shows Raman spectra of co-precipitated silicate materials containing 0.5%, 0.75, 0.875, and 1.0% barium chloride monohydrate BWOB according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] definition Where the definition of a term deviates from the meaning of the term in common usage, applicants intend to utilize the definition provided below, unless otherwise indicated.

[0009] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit any of the claimed subject matter. In this application, the use of the singular includes the plural unless expressly stated otherwise. It should be noted that as used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. In this application, the use of "or" means "and / or" unless expressly stated otherwise. Furthermore, the use of the term "including" as well as other forms such as "include," "includes," and "included" are not limiting.

[0010] As used herein, the terms "comprising," "having," and "including," as well as variations of these words, are open-ended and mean that there may be additional elements other than the listed elements.

[0011] In the present disclosure, directional terms such as "top", "bottom", "upper", "lower", "above", "below", "left", "right", "horizontal", "vertical", "up", "down" and the like are used only for convenience in describing various embodiments of the present disclosure. The embodiments of the present disclosure may be oriented in various ways. For example, the diagrams, devices, etc. shown in the drawings may be flipped, rotated 90 degrees in any direction, or inverted.

[0012] For purposes of this disclosure, a value or characteristic is "based" on a particular value, characteristic, satisfaction of a condition, or other factor if the value is derived by performing a mathematical calculation or logical decision using the value, characteristic, or other factor.

[0013] For the present disclosure, in order to provide a more concise description, it should be noted that some quantitative expressions shown herein are not modified with the term "about". Regardless of whether the term "about" is explicitly used, all quantities given herein are meant to refer to the actual given value, and also to refer to approximations to the given value as reasonably estimated based on ordinary skill in the art, including approximations based on experimental and / or measurement conditions for such given value.

[0014] For purposes of this disclosure, the term "actual temperature" refers to the actual temperature of the air at any particular location, as measured by a thermometer.

[0015] For the purposes of this disclosure, the term "BWOB" refers to "by weight of binder," which is commonly recognized as the amount (percentage) of material added to cement when that material is added based on the total amount of a particular binder or blend of binders. In the case of geopolymer materials, the binder is typically a pozzolanic material called a pozzolanic precursor that can be activated with an alkaline solution.

[0016] For the purposes of this disclosure, the term "cement" refers to a binder, a substance used in construction that hardens, sets, and adheres other materials to bind them together. Cement is rarely used alone and may be used to bind sand and gravel (aggregates). Cement mixed with fine aggregate produces mortar for masonry or with sand and gravel to produce concrete. Cements used in construction are typically inorganic, often lime or calcium silicate based, and can be characterized as hydraulic or nonhydraulic, depending on the ability of the cement to hydrate in the presence of water.

[0017] For the purposes of this disclosure, the term "concrete" refers to a heavy, coarse building material made from a mixture of broken stone or gravel, sand, cement materials, and water that can be spread or poured into forms and forms a stone-like mass upon hardening. Some embodiments may include a composite material composed of fine and coarse aggregates bound together with a flowable cement (cement paste) that hardens over time. Most frequently Portland cement may be utilized, although other hydraulic cements such as calcium aluminate cements may sometimes be used. Geopolymers are believed to be a new type of cementitious material that does not include Portland cement.

[0018] For the purposes of this disclosure, the term "geopolymer" refers to a sustainable cement binder system that does not contain Portland cement. In a narrower sense, the geopolymers of the disclosed invention relate to inorganic polymers that have a three-dimensional network structure similar to organic thermosetting polymers. The backbone matrix of the disclosed geopolymers is an X-ray amorphous analogue of the zeolite framework, characterized by tetrahedral coordination of Si and Al atoms linked by oxygen bridges, with AlO4 - Associated alkali metal cations (usually Na) as charge balancers for + and / or K + The geopolymers of the disclosed invention may be more broadly considered as a class of alkali-activated materials (AAMs) composed of alkali aluminosilicate and / or alkali alkaline earth aluminosilicate phases as a result of the reaction of solid aluminosilicate powders (terminology pozzolanic precursors) with an alkali activator.

[0019] For the purposes of this disclosure, the term "geopolymer composition" refers to a mixture of pozzolanic precursors in solid or liquid form and an alkaline activator in proportions. Additionally, the geopolymer composition may further include fine and coarse aggregates, fibers, and other admixtures depending on the application.

[0020] For the purposes of this disclosure, the term "mortar" refers to a workable paste containing fine aggregates used to bind building blocks such as stones, bricks, and concrete blocks, fill and seal irregular gaps between them, and sometimes add decorative color and patterns in masonry walls. In the broadest sense, mortar includes soft muds or clays such as those used between pitch, asphalt, and mud bricks. Cement or geopolymer mortar hardens into a solid structure as it cures.

[0021] For the purposes of this disclosure, the term "room temperature" refers to a temperature between about 15° C. (59° F.) and 25° C. (77° F.).

[0022] For the purposes of this disclosure, the term "setting" refers to the transformation of a plastic paste into a non-plastic, rigid body.

[0023] For the purposes of this disclosure, the term "set time" or "setting time" refers to the time that elapses from the moment that water (alkaline activator solution) is added to the cement (pozzolanic precursor) to the time that the paste begins to lose its plasticity (initial set). The final set time is the time that elapses from the moment that water (alkaline activator solution) is added to the cement (pozzolanic precursor) to the time that the paste completely loses its plasticity and reaches a hardness sufficient to withstand a certain pressure.

[0024] For the purposes of this disclosure, the term "poorly soluble in water" refers to a substance that has a solubility of 0.1 g per 100 ml of water to 1 g per 100 ml of water. Unless otherwise specified, the terms "poorly soluble" and "poorly soluble in water" are used interchangeably in the following description of the invention to refer to a substance that is poorly soluble in water.

[0025] For the purposes of this disclosure, the term "water-insoluble" refers to a substance that has a solubility of less than 0.1 g in 100 ml of water.

[0026] explanation While the invention is susceptible to various modifications and alternative forms, specific embodiments thereof are shown by way of example in the drawings and are described in detail below. It is to be understood, however, that it is not intended to limit the invention to the particular forms disclosed, but on the contrary, the invention is to cover all modifications, equivalents, and alternatives falling within the spirit and scope of the invention.

[0027] Geopolymers are a class of alkali-activated binders that have a three-dimensional network structure similar to that of organic thermosetting polymers. The backbone matrix of geopolymers is an X-ray amorphous analogue of the zeolite framework, characterized by tetrahedral coordination of Si and Al atoms linked by oxygen bridges, resulting in AlO4 -Associated alkali metal cations (usually Na) as charge balancers for + and / or K + ) Nominally, the empirical formula of geopolymer is M n [-(SiO2) z -AlO2] n It can be expressed as ·wH2O, where M represents an alkali cation, z represents the molar ratio of Si to Al (1, 2 or 3), and n represents the degree of polycondensation. Dissolution of reactive low-Ca aluminosilicate sources by alkaline hydrolysis consumes water and produces aluminate and silicate species. This first stage of geopolymerization is controlled by the ability of alkaline compounds to dissolve the fly ash glass network and generate small reactive species of silicate and aluminate: [ka] Upon dissolution, these species become part of the aqueous phase, i.e. the activated solution already containing silicates. This results in the formation of a complex mixture of silicate, aluminate and aluminosilicate species. As the aqueous phase species form larger networks by polycondensation, the solution becomes more and more concentrated, resulting in the formation of an alkali aluminosilicate gel (AAS): [ka] After gelation, the system continues to reconfigure and reorganize due to increased connectivity of the gel network, resulting in a three-dimensional aluminosilicate network that hardens and solidifies during the subsequent curing process.

[0028] Examples of these low-Ca reactive aluminosilicates include metakaolin (MK), certain calcined zeolites, and low-Ca Class F fly ash (low-Ca FFA).

[0029] Metakaolin is an amorphous aluminosilicate pozzolanic material whose use dates back to 1962 when it was incorporated into the concrete of the Jupiter Dam in Brazil. It is a thermally activated aluminosilicate material with high pozzolanic activity comparable to, but not exceeding, that of fumed silica. Metakaolin is produced by calcining kaolinite clay at 650°C-800°C, depending on the purity and crystallinity of the precursor clay. Alkaline activation of metakaolin produces a typical AAS gel composition that hardens and solidifies at ambient temperature. The mechanical properties and microstructure of the geopolymers are strongly dependent on the initial Si / Al molar ratio. Better strength properties have been reported for mixtures with a molar ratio of M2O / Al2O3 of approximately 1 and a SiO2 / Al2O3 ratio in the range of 3.0-3.8.

[0030] Fly ash is a fine powdery material that "fizzes" out of coal combustion chambers (boilers) and is captured by emission control systems such as electrostatic precipitators and fibrous filter "baghouses" and scrubbers. Approximately 131 million tons of fly ash are produced annually, of which approximately 56 million tons are recycled. Worldwide, approximately 65% ​​of the fly ash produced is disposed of in landfills or ash ponds. Anthracite and bituminous coal combustion typically produces Class F fly ash, which has less than 8% CaO. Fly ash is composed primarily of glassy, ​​spherical particles. The American Society for Testing and Materials (ASTM) C618 standard recognizes two major classes of fly ash, Class C and Class F. Class F fly ash (FFA: F fly ash) has a lower limit of (SiO2+Al2O3+Fe2O3) of 70%, while Class C fly ash (CFA) has a lower limit of 50%. High calcium oxide content results in Class C fly ash with cementitious properties that result in the formation of calcium silicate and calcium aluminate hydrates when mixed with water without the need for alkali activation. US Patent No. 5,435,843 discloses alkali-activated Class C fly ash compositions with initial cement setting times of less than about 5 minutes. Generally, Class F fly ashes have a maximum calcium oxide content of about 18% by weight, while Class C fly ashes generally have a higher calcium oxide content, such as 20-40% by weight. Low-Ca FFAs typically contain CaO in proportions of less than 8% by weight. Low-Ca FFA-based geopolymers are typically very slow to cure and harden, and have low ultimate strengths when cured at ambient temperatures (e.g., room temperature), but their reactivity increases with increasing curing temperatures. To produce useful construction materials, alkali activation of low-Ca FFAs requires high temperature curing. Alternatively, to produce geopolymer products that harden and set at ambient temperatures, they must be blended with more reactive aluminosilicate materials such as fine blast furnace slag (BFS) powder or metakaolin.

[0031] Ground granulated blast furnace slag is another type of reactive aluminosilicate material rich in alkaline earth oxides such as CaO and MgO. Ground granulated blast furnace slag is a glassy granular material that varies from a popcorn-like crumbly coarse structure to dense sand-sized particles with diameters of over 4.75 mm. When ground, the particle size is reduced to a cement fineness and can be used as a supplemental cementitious material in Portland cement-based concrete. Blast furnace slag is essentially a calcium aluminosilicate glass, typically containing 27-38% by weight SiO2, 7-12% by weight Al2O3, 34-43% by weight CaO, 7-15% by weight MgO, 0.2-1.6% by weight Fe2O3, 0.15-0.76% by weight MnO, and 1.0-1.9% by weight SiO2. Blast furnace slag is usually classified into three grades according to ASTM C989-92: 80, 100 and 120. Furthermore, ultra-fine blast furnace slag is more reactive compared to BFS 120. For example, MC-500® Microfine® cement (de Neef Construction Chemicals) has a particle size of less than about 10 μm and a specific surface area of ​​about 800 m 2 / kg of ultra-fine pulverized coal. BFS is nearly 100% vitreous and therefore generally more reactive than most fly ashes. Alkaline activation of BFS essentially produces calcium silicate hydrate (CSH) and calcium aluminosilicate (CASH) gels. Geopolymers produced by alkaline activation of BFS typically harden and set very rapidly even at ambient temperatures, resulting in much higher ultimate strengths than geopolymers produced with low Ca Class F fly ash. Some compositions have initial hardening times of less than 60 minutes, making them difficult to mix, place and finish. Alkaline-activated slag has been found to have several superior properties compared to Portland cement concrete, including low heat of hydration, high early strength and superior durability in aggressive environments. 1 A review of published literature showed that this binder system has some serious drawbacks, such as rapid hardening and high drying shrinkage. 2,3These issues must be resolved before it can be used in commercial operations.

[0032] Recently, the use of lignite and subbituminous coals has increased significantly, and a significant percentage of U.S. coal reserves produce fly ash containing significant amounts of CaO. Fly ash containing high CaO content, e.g., greater than 8% but less than 20% by weight (high-Ca FFA), may still be classified as Type F by ASTM C-618. The setting time of fly ash-based geopolymers decreases exponentially with increasing CaO content, but compressive strength increases with increasing CaO. 4 According to the disclosed embodiments, it has been found that fast setting can occur in fresh geopolymers made with high Ca FFAs containing 12.2 wt% CaO. Geopolymers made with CFAs with greater than 20% CaO typically set within 36 minutes, and fast setting, e.g., within a few minutes, is quite common. 5 Clearly, geopolymers made with high-Ca FFAs (e.g., greater than 8% CaO) and CFAs require proper curing control to produce useful construction materials. 6 Alkaline activation of high-Ca FFAs produces hydrated products such as CSH and CASH along with alkali aluminosilicate gels. The setting time of the geopolymer depends on the properties of the alkali activator solution, such as alkali molarity, SiO2 / M2O (M=Na,K) molar ratio, and binder to water ratio (w / b). For example, setting time decreases with increasing alkali hydroxide molarity and SiO2 / M2O (M=Na,K) molar ratio, but increases with increasing w / b. Conversely, the compressive strength of the set geopolymer increases with increasing alkali hydroxide molarity and SiO2 / M2O (M=Na,K) molar ratio.

[0033] Class C fly ash has some similarities to blast furnace slag. Both are calcium aluminosilicate glasses. These pozzolanic materials are called reactive alkaline earth aluminosilicates, or high-Ca reactive aluminosilicates. In addition to BFS and CFA, high-Ca FFA, vitreous calcium silicate (VCAS), and clinker kiln dust (CKD) fall into this category. VCAS is a waste product associated with fiberglass manufacturing. In a typical fiberglass manufacturing facility, typically about 10-20% by weight of the processed glass material is not converted into the final product and is rejected as a by-product or waste VCAS and sent to landfill. VCAS is 100% amorphous and its composition is very consistent, containing mainly about 50-55% SiO2, 15-20% Al2O3, and 20-25% CaO by weight. When tested according to ASTM C618 and C1240, ground VCAS exhibits pozzolanic activity comparable to silica fume and metakaolin. CKD is a by-product and industrial waste product of Portland cement manufacturing. Over 30 million tons of CKD are produced annually worldwide, with a significant amount ending up in landfills. A typical CKD contains approximately 38-64 wt% CaO, 9-16 wt% SiO2, 2.6-6.0 wt% Al2O3, 1.0-4.0 wt% Fe2O3, 0.0-3.2 wt% MgO, 2.4-13 wt% K2O, 0.0-2.0 wt% Na2O, 1.6-18 wt% SO3, and 0.0-5.3 wt% Cl. - and has 5.0-25 wt% LOI. CKD is generally a very fine powder (e.g., about 4600-14000 cm 2 During alkaline activation, CSH gel, ettringite (3CaO·Al2O3·3CaSO4·32H2O), and / or syngenite (mixed alkali-calcium sulfate) will further form.

[0034] In general, geopolymers made by alkaline activation of these reactive high-Ca aluminosilicates harden and set very quickly due to the instantaneous formation of calcium silicate hydrate and calcium aluminosilicate hydrate gels. In engineering practice, the setting time of geopolymers should be fairly long. This means that concrete or mortar made with pozzolanic binders needs a long enough setting time to allow transportation and placement. However, too long a setting time is uneconomical. According to the disclosed embodiments, proper control of setting time by using set retarders is very important for the effective application of geopolymer materials in the construction and building industry.

[0035] Setting time control can be achieved by properly formulating the activator solution composition for high-Ca aluminosilicate-based geopolymers. For example, a high w / b and low alkali silicate concentration may result in a geopolymer paste with sufficient setting time and workability. However, the performance of the set product is usually greatly affected, and significant strength loss and large drying shrinkage can be expected. In recent years, various types of admixtures have been used to retard the setting of alkali-activated cements or geopolymers, but their retardation efficiency varies widely. 3 U.S. Patent No. 5,366,547 discloses a method of retarding the setting time of sodium hydroxide-activated blast furnace slag using phosphate additives. Examples of phosphate retarders include sodium metaphosphate, sodium polyphosphate, potassium metaphosphate, and potassium polyphosphate. The retarding effect of these phosphate additives may change when sodium silicate solutions are used to activate BFS or other types of high Ca aluminosilicates. Kalina et al. 7 used Na3PO4 to retard the setting of sodium silicate-activated blast furnace slag. Solid sodium phosphate was blended with BFS and then mixed with sodium silicate activator solution. When high doses of retarder were applied to achieve long setting or workable times, the compressive strength was significantly affected (reduced). Chang 8 and Chang et al.9 concluded that the use of phosphoric acid alone extends the hardening time of alkali-activated slags after the critical concentration is reached, but reduces the compressive strength at early ages. 2+ The ions were assessed to be bound to the phosphate anions from the retarder. The formation of calcium dihydrogen and later hydrogen phosphate structures results in a lack of dissolved calcium ions, which hinders the nucleation and growth of CSH and CASH, thus prolonging the initial setting time.

[0036] The efficiency of certain retarders commonly used with Portland cement varies with geopolymers. Most set-retarding admixtures that are effective with Portland cement may not work in highly alkaline geopolymer systems. Wu et al. 10 observed that potassium tartrate or sodium tartrate did not affect the initial setting time of alkali-activated slags, but slightly reduced the final setting time. 11 found that sucrose and gypsum, which work well with Portland cement, do not extend the setting time for sodium silicate-activated high-Ca FFAs. Brought et al. 12 investigated the retarding effect of NaCl on the setting time of a sodium silicate-activated slag system. The addition of NaCl at high dosages significantly retarded both setting and strength development, whereas at low dosages, i.e., below 4% by weight of the slag, NaCl acted as an accelerator. In another sodium silicate-activated slag system, 13 Little effect of NaCl on hardening time was observed at additions up to 20% by weight of binder (BWOB), beyond which hardening was retarded. However, the addition of such large amounts of chloride to reinforced geopolymer concrete may result in significantly accelerated corrosion of the rebar, thereby shortening its service life.

[0037] The use of borates as retarders for Portland cement is also very well known. However, Nicholson et al. 14reported that borate added to alkali-activated fly ash (Class C) does not affect the hardening behavior, and conversely, the strength of the binder is adversely affected by large amounts of borate salts. U.S. Patent No. 4,997,484 discloses an alkali hydroxide-activated Class C fly ash geopolymer composition (containing no soluble silicates). The geopolymer composition uses borax as a retarder, but exhibits rapid strength gains, such as 1800-4000 psi after curing at 73°F for 3-4 hours. Boron retarders were not effective in retarding the hardening of alkali-activated CFA geopolymers. U.S. Patent No. 7,794,537 and U.S. Patent No. 7,846,250 both disclose certain chemical compounds as well-known retarders for Portland cement and geopolymers. The geopolymer compositions are MK or FFA based for oil field applications or carbon dioxide storage. These compounds retard the thickening of well cementing grout at high temperatures, such as 85°C, and include borax (Na2B4O7·10H2O), boric acid, sodium phosphate, and lignosulfonates.

[0038] US Patent Application No. 2011 / 0284223 discloses compositions and methods for well cementing applications that use organic compounds to retard thickening of geopolymer systems at elevated temperatures. Geopolymer compositions are not new, having been disclosed in the prior art and widely studied in the literature. Preferred compounds as retarders include aminated polymers, phosphonated amines, quaternary ammonium compounds, and tertiary amines. While the geopolymer composition itself is not unique, the effect of these retarders on hardened properties such as compressive strength has not been previously developed / communicated.

[0039] Chinese Patent No. 102249594B discloses a composite retarder for delaying the setting time of alkali-activated blast furnace slag. The composite retarder is composed of sodium chromate, heterocyclic amino acid and silicone surfactant. Chinese Patent No. 1118438C discloses a composite retarder consisting of potassium chromate, sugar and phenol for sodium silicate activated slag. The initial setting can be adjusted between 1 hour and 70 hours. However, retarders can be undesirable because chromate is a highly mobile, easily mobile and toxic anionic species, which poses the risk of polluting the environment. Chinese Patent Application No. 101723607A discloses soluble zinc salts for delaying the setting time of sodium silicate activated blast furnace slag. These zinc salts include nitrates, sulfates and chlorides. Chinese Patent Applications Nos. 1699251A and 100340517C disclose barium salts as retarders for alkali-activated carbonite / blast furnace slag. Either the zinc salt or the barium salt is dissolved in water and added to the blast furnace slag. An alkaline activator solution is then added to the mixture. Alternatively, salt powder is ground with the blast furnace slag. The activator solution is then mixed with the solid blend.

[0040] Unfortunately, most retarders in the prior art were developed only for alkali-activated slag. It is well known that the efficiency of retarders is highly dependent on the binder composition. Retarder that is effective with Portland cement and alkali-activated slag does not necessarily work well in geopolymer systems such as those made with high-Ca FFA, CFA, or blends of low-Ca FFA and BFS.

[0041] The methods disclosed in the prior art mainly employ two important mechanisms to retard the setting time of alkali-activated slag. The retarders are the released Ca 2+ is added to chelate and / or precipitate Ca 2+The calcium activator prevents the silicone surfactant from reacting with silicate species already present in the alkaline activator solution. In another method, a retarder is added to form a protective layer directly bonded to the surface of the anhydrous blast furnace slag particles, thereby reducing their ability to dissolve in highly alkaline solutions. These attached layers can be either adsorbed species or insoluble calcium salts that precipitate and adhere to the surface. This method is referred to herein as "protective layers". Chinese Patent No. 102249594B describes how silicone surfactants are adsorbed onto the surface of blast furnace slag particles, and when a charger is introduced, the resulting repulsive forces cause the Ca 2+ It is disclosed that the Ca released during the dissolution of blast furnace slag in a highly alkaline environment is absorbed by the slag and the Ca(II) is released from the slag, and the Ca(II) is released from the slag ... 2+ The cations bind to the phosphate anions from phosphate retarders, e.g., Na3PO4. The formation of insoluble calcium phosphate compounds reduces the available Ca 2+ This reduces the nucleation and growth of the CSH phase, thus extending the hardening time. 7 Boron compounds dissolved in alkaline solutions form tetrahydroxyborates, which react with Ca 2+ The precipitated calcium borate (e.g., Ca(B[OH]4)2H2O) partially or completely covers the surface of the blast furnace slag particles. The presence of such an impermeable calcium borate layer therefore prevents further dissolution of the blast furnace slag particles in the alkaline solution. 15 Soluble zinc salts are converted to calcium zincate phases (e.g., CaZn2(OH)6·H2O) and partially or completely cover the blast furnace slag particles, thus passivating them against further hydration or alkaline activation. 16,17US Patent Application No. 20160060170 discloses a geopolymer composition with nanoparticle retarders to control the setting time. Reactive aluminosilicates include metakaolin, fly ash or rice husk ash. The reactive aluminosilicate particles are coated with nanoparticles such as halloysite nanotubes and kaolin nanoclay particles before mixing with the sodium silicate activator solution. The nanoparticle coating is to retard the geopolymerization reaction. A barium salt solution is premixed with the blast furnace slag / carbonatite powder. The surface of the blast furnace slag particles is negatively charged in water, so the Ba 2+ Cations tend to adsorb onto the surface of slag particles. When exposed to alkaline silicate solutions, insoluble barium precipitates form a thin film on the slag particles, preventing the slag from coming into contact with the alkaline solution (Chinese Patent Application No. 1699251A).

[0042] When the formation of a protective layer on the surface of the pozzolan particles is used to slow the setting time of the alkali-activated material, a solution of a metal salt such as barium nitrate should be mixed with the pozzolan particles prior to mixing with the alkali silicate solution to improve coverage of the protective coating.

[0043] The disclosed embodiments provide a new method of using metal salts to delay the setting time of alkali-activated materials or geopolymers. The rapid setting of alkali-activated Ca-rich reactive aluminosilicates is associated with the formation of CSH and / or CASH gels during early setting. The Ca-rich reactive aluminosilicate particles dissolve during dissolution. 2+ Cations are released, which react almost instantly with the silicate anions present in the alkaline solution. The control of hardening is achieved by, for example, the addition of Ca 2+ This can be achieved by prior art methods through the removal of ions and / or the formation of a protective layer on the surface of the pozzolan particles. Control of hardening can also be achieved by controlling the availability of silicic acid species for the nucleation and growth of the CSH and / or CASH gel. For example, methods disclosed for well cementing geopolymers include 18In this method, powdered alkali silicate glass is used. The geopolymer paste contains almost no silicate species during early setting. The powdered alkali silicate glass dissolves and releases silicic acid species at a controlled rate during early setting, thus extending the thickening and setting time. However, this method produces a set geopolymer that is not suitable for construction material applications requiring strengths above 30 MPa. Alternatively, metal salts (e.g., barium chloride) are dissolved in water and the resulting solution is then blended with the alkali silicate solution before mixing with the dry ingredients in a mixer. These metal salts, such as barium chloride, hydrolyze in the alkaline solution and the silicate anions co-precipitate during hydrolysis, leaving an activator solution depleted of silicic acid species. The extent of the metal-silicate interaction depends on the metal / Si molar ratio, which determines the efficiency of the retardation. The co-precipitated silicates slowly re-dissolve and become available for geopolymerization and / or formation of CSH and / or CASH gels during the subsequent setting process. This extends the setting time.

[0044] The disclosed method requires much less barium salt to reach the same setting time as the "protective layer" method disclosed in Chinese Patent Applications Nos. 101723607A, 1699251A and 100340517C, where the metal salt solution must be premixed with the solid, i.e., blast furnace slag, which provides a protective coating to the pozzolan particles. For example, at least 2% BWOB zinc salt provides retardation with sodium silicate-activated blast furnace slag. At least 4% BWOB barium salt provides retardation with sodium silicate-activated blast furnace slag / carbonatite. A higher amount of retarder is needed to achieve good coverage of the protective layer, but this usually results in a significant decrease in the compressive strength of the hardened product. Furthermore, the coverage of the protective layer is highly dependent on the surface charge of the pozzolan particles. The surface charge of blast furnace slag can be negative, whereas the surface charge of fly ash can be positive in solution. Thus, in the "protective layer" method, the efficiency of the retardation effect can vary greatly with different reactive aluminosilicate sources.

[0045] Thus, the disclosed embodiments provide an efficient inorganic retarding admixture for adjusting the thickening and setting time of geopolymer compositions that can be applied as well bore cementing grouts, mortars and concretes.

[0046] Other embodiments described herein provide a geopolymer composition whose setting time can be altered by an inorganic retarder. The geopolymer composition includes (i) at least one low-Ca class F fly ash having 8 wt% or less calcium oxide, (ii) at least one high-Ca aluminosilicate selected from the group of blast furnace slag, class C fly ash, vitreous calcium silicate, and kiln dust, (iii) a retarding solution, and (iv) an aqueous alkaline silicate activator.

[0047] The disclosed retarder solutions are made by dissolving at least one soluble metal salt in water, the at least one soluble metal salt being selected from barium chloride, barium chloride dihydrate, barium nitrate, barium nitrite, barium metaborate monohydrate, barium nitrate hydrate, zinc nitrate, zinc chloride, zinc sulfate, lead chloride, lead nitrate, strontium chloride, strontium nitrate and strontium sulfate. Barium chloride and barium nitrate are preferred.

[0048] In one embodiment, at least one metal salt is dissolved in the retarder solution, and the retarder solution comprises about 0.1 to about 10% of the metal salt BWOB. In one embodiment, the metal salt is barium chloride dihydrate. The dosage of barium chloride dihydrate is about 0.10 to about 5% BWOB, more preferably about 0.5% to about 2.5% BWOB.

[0049] In one embodiment, a soluble barium salt is dissolved in water. The retarder solution is mixed with the alkali silicate activator solution before the activator solution is mixed with all other ingredients. In another embodiment, the retarder solution and the activator solution are added separately when mixed with the dry ingredients. The alkali silicate activator solution may include a metal hydroxide and a metal silicate, where the metal is potassium, sodium or a combination of both.

[0050] The disclosed embodiments provide a geopolymer composition comprising: (i) at least one high Ca aluminosilicate selected from the group of BFS, CFA, vitreous calcium silicate, and kiln dust; (ii) a retarder solution; and (iii) an alkali silicate solution.

[0051] In one disclosed embodiment, the geopolymer composition comprises (i) at least one high Ca aluminosilicate selected from the group consisting of BFS, CFA, vitreous calcium silicate, and kiln dust, (ii) metakaolin, (iii) a retarder solution, and (iv) an alkali silicate solution.

[0052] In one disclosed embodiment, the geopolymer composition further comprises fine and / or coarse aggregates, superplasticizers or fibers to produce mortar and concrete for construction applications.

[0053] One disclosed embodiment provides high and ultra high performance concrete compositions whose set time can be adjusted by inorganic retarders. The high and ultra high performance concrete compositions include (i) blast furnace slag, (ii) metakaolin, (iii) a retarding solution, (iv) an aqueous alkali silicate activator, (v) at least one aggregate, and (vi) at least one micron / submicron filler.

[0054] The objective of the present disclosure is to provide an effective retarding admixture for adjusting the setting time of geopolymer compositions that may be applied as well cementing, mortars, and concretes. In particular, the present disclosure provides an efficient retarding method for controlling the setting of geopolymer systems containing high Ca FFAs or high Ca aluminosilicates.

[0055] Low Ca fly ash based geopolymer Due to the low reactivity of fly ash in alkaline solutions, low-Ca FFA-based geopolymers are very slow to set and harden, and have low final strengths when cured at low temperatures (e.g., room temperature). "Reactivity" is defined herein as the relative mass of binder pozzolana reacted with alkaline solution. Fly ash with smaller particle size is usually more reactive, such as ultrafine fly ash (UFFA) with an average particle size of about 1-10 μm. UFFA is carefully processed by mechanically separating the ultrafine fraction from the parent fly ash. UFFA can also be reduced in w / b ratio for desirable workability such as slump, producing hardened geopolymers with better performance. Coal gasification fly ash is typically discharged from coal gasification power plants as SiO2-rich, substantially spherical particles with a maximum particle size of about 5-10 μm. To use less reactive fly ash, a more reactive second binder is required to produce a geopolymer product that can be cured at ambient temperatures.

[0056] Alkaline activation of metakaolin produces typical geopolymer gels with moderately long setting times, e.g., 2-6 hours. When metakaolin is blended, the resulting geopolymer composition may not require a retarding admixture. In contrast, alkaline activation of BFS, CFA, CKD, or VCAS essentially produces CSH and / or CASH gels. Rapid precipitation of CSH and / or CASH reduces the setting time and improves the strength gain rate and final strength of the product. When the second binder is a high Ca aluminosilicate pozzolan, the setting behavior of the resulting geopolymer system will be significantly modified. The setting time of fly ash-based geopolymers decreases exponentially with increasing amounts of high Ca aluminosilicate pozzolan such as BFS blended, especially when alkaline activator solutions with high molar alkali hydroxide and high SiO2 / M2O (M=Na, K) molar ratios are used to produce useful geopolymer products. Thus, proper setting control will be required in practical applications.

[0057] In one embodiment, the low Ca FFA can be a fly ash containing about 8 wt. % calcium oxide or less. The classification of fly ash is based on ASTM C618 as generally understood in the art. In one embodiment, the low Ca FFA contains about 5 wt. % calcium oxide or less. In one embodiment, the fly ash should contain at least 65 wt. % amorphous aluminosilicate phase and have an average particle size of 60 μm or less, such as 50 μm or less, such as 45 μm or less, such as 30 μm or less. In one embodiment, the low Ca FFA has a loss on ignition (LOI) of 5% or less. In one embodiment, the low Ca FFA has a LOI of 1% or less.

[0058] An embodiment described herein provides a geopolymer composition whose setting time can be adjusted by an inorganic retarder. The low-Ca FFA based geopolymer composition includes (i) at least one low-Ca class F fly ash having 8% or less by weight calcium oxide, (ii) at least one high-Ca aluminosilicate selected from the group of blast furnace slag, class C fly ash, vitreous calcium silicate, and kiln dust, (iii) a retarder solution, and (iv) an aqueous alkali silicate activator. The retarder solution is made by dissolving a soluble metal salt in water, the soluble metal salt being selected from barium chloride, barium chloride dehydrate, barium nitrate, barium nitrite, barium metaborate monohydrate, barium nitrate hydrate, zinc nitrate, zinc chloride, zinc sulfate, strontium chloride, strontium nitrate, and strontium sulfate. Soluble barium salts are preferred.

[0059] In one embodiment, the low Ca FFA based geopolymer composition further comprises metakaolin, and in one embodiment, the geopolymer composition further comprises fine and coarse aggregates for producing a concrete product.

[0060] High Ca aluminosilicate based geopolymer Alkaline activation of high Ca aluminosilicate pozzolans usually produces CSH and / or CASH gels quickly upon exposure to highly alkaline solutions, resulting in very short setting times. Without proper control of setting time, these geopolymeric materials cannot be used to manufacture useful products. Examples of these high Ca aluminosilicates include high Ca FFA, CFA, BFS, VCAS, bottom ash, and clinker kiln dust (CKD).

[0061] One embodiment provides a high Ca aluminosilicate based geopolymer composition comprising: (i) at least one high Ca aluminosilicate selected from the group of high Ca FFA, BFS, CFA, vitreous calcium silicate, and kiln dust; (ii) a retarder solution; and (iii) at least one alkali silicate solution.

[0062] In one embodiment the Ca-rich aluminosilicate is a Ca-rich FFA, in one embodiment the Ca-rich aluminosilicate is a BFS, and in another embodiment the Ca-rich aluminosilicate is a CFA.

[0063] In one embodiment, the high Ca aluminosilicate based geopolymer composition further comprises at least one low Ca aluminosilicate pozzolan selected from the group of low Ca FFA and metakaolin. In one embodiment, the high Ca aluminosilicate based geopolymer composition further comprises fine and coarse aggregates for producing a concrete product. In one embodiment, the geopolymer composition further comprises fine and / or coarse aggregates for producing a concrete product.

[0064] High and Ultra High Performance Concrete US Patent No. 9,090,508 discloses geopolymer compositions for high and ultra-high performance concrete. To achieve high and ultra-high performance of geopolymer products, highly reactive aluminosilicate materials such as metakaolin and blast furnace slag must be used as binders. The w / b ratio must be very small, i.e. close to minimum. The packing density of the particulates must be high to minimize the porosity of the product, and no coarse aggregates larger than 10 mm should be used to promote uniformity. Thus, the setting time of the ready mixed concrete is relatively short, especially when a large amount of blast furnace slag is used in the mix. The compositions disclosed in US Patent No. 9,090,508 are essentially binary geopolymers based on blast furnace slag / metakaolin.

[0065] One embodiment described herein provides high and ultra high performance concrete compositions whose set time can be adjusted by inorganic retarders. The high and ultra high performance concrete compositions include (i) blast furnace slag, (ii) metakaolin, (iii) a retarding solution, (iv) an aqueous alkali silicate activator, (v) at least one aggregate, and (vi) at least one micron / submicron filler.

[0066] How to place the retarder The retarder solution is prepared by dissolving at least one soluble metal salt in water, the at least one soluble metal salt being selected from barium chloride, barium chloride dehydrate, barium nitrate, barium nitrite, barium metaborate monohydrate, barium nitrate hydrate, zinc nitrate, zinc chloride, zinc sulfate, lead chloride, lead nitrate, strontium chloride, strontium nitrate and strontium sulfate. Any soluble metal salt that can be hydrolyzed in an alkaline solution and co-precipitate the silicate species originally present in the alkaline silicate activator solution can be used as an inorganic retarder admixture. The retardation effect depends on the type and dosage of the metal. The interaction of the metal with the silicate is expected to increase with increasing dosage or molar ratio of the metal to the silicate. The interaction of the metal with the silicate should not be excessive. If the interaction is overwhelming, the release of silicate species into the geopolymer system will be greatly hindered during the subsequent hardening process, significantly affecting the early compressive strength of the product.Of all these metal salts, the barium salts are preferred.

[0067] In one embodiment, at least one metal salt is dissolved in water. The retarder solution is mixed with the alkali silicate activator solution before all ingredients are mixed. The alkali silicate activator solution combined with the retarder solution is poured into the mixer containing all dry ingredients. In another embodiment, the retarder solution and the activator solution are added separately when mixed with the dry ingredients to produce the geopolymer product.

[0068] In one embodiment, the retarder solution is mixed with the alkali silicate activator solution for about 30 minutes before mixing with all other ingredients. In another embodiment, the retarder solution is mixed with the alkali silicate activator solution for about 10 minutes before mixing with all ingredients. In another embodiment, the retarder solution is mixed with the alkali silicate activator solution for about 24 hours before mixing with all ingredients. In another embodiment, the retarder solution is added to the concrete while it is being mixed in the ready-mix truck. In this case, the retarder solution acts as a setting brake, preventing the mixed concrete from setting in the ready-mix truck during transport to the site of an emergency, etc.

[0069] In one embodiment, at least one metal salt is included in the retarder solution, and the retarder solution comprises about 0.1 to about 10% of the metal salt BWOB. In one embodiment, the metal salt is barium chloride dihydrate. The dosage of barium chloride dihydrate is about 0.10 to about 5% BWOB, more preferably about 0.5% to about 2.5% BWOB.

[0070] In one embodiment, the metal salt is barium metaborate monohydrate, in one embodiment the retarder solution includes barium chloride dihydrate and zinc nitrate, and in one embodiment the retarder solution includes strontium nitrate and zinc chloride.

[0071] Delay Mechanism The following example illustrates the mechanism for retarding the setting time of the geopolymers of the present disclosure.

[0072] According to the disclosed embodiments, a new method is provided to control the setting time of alkali-activated materials or geopolymers by using metal salts to control the release of silicate species in the activator solution that are available for nucleation and growth of CSH and / or CASH gels during early setting. In selected embodiments, experiments were performed to study the co-precipitation process of hydrolyzed barium chloride and silicates in sodium silicate activator solutions by Raman spectroscopy. In one series of tests, barium chloride dehydrate solutions and sodium silicate solutions were mixed for 0.5 hours, and then the Raman spectra of the supernatant liquid and precipitate were monitored with increasing doses of barium chloride. In a second series of tests, combined solutions of barium chloride and sodium silicate solutions were mixed and aged with a fixed dose of barium chloride dihydrate for 0.5 hours, 2 hours, and 24 hours, respectively. The spectra of the supernatant liquids of these barium chloride / sodium silicate solutions were then recorded.

[0073] Sodium hydroxide beads (99% purity) were dissolved in DI (deionized) water and combined with type Ru sodium silicate solution from PQ Corp to prepare a sodium silicate activator solution. Barium chloride dihydrate (99% purity) was dissolved separately in DI water. The composition of the activator solution is shown in Table 1. The molar concentration of NaOH was fixed at 5 and the mass ratio of SiO2 / Na2O was 1.25 throughout Examples 1-4. The activator solutions used in the tests were part of the high Ca FFA geopolymer composition and the dosage of barium chloride dehydrate was expressed as the weight of the fly ash binder. [Table 1]

[0074] Raman spectra were collected using a single grating spectrometer-notch filter micro-Raman system. Melles-Griot model 45 Ar +The laser provided incident light at 5145 Angstrom wavelength that was directed through a broadband polarization rotator (Newport model PR-550) into a laser microscope that directed the laser light through a long working distance Mitutoyo 10 microscope objective onto the precipitated solid or solution in a 25 ml clear vial. The laser light power was approximately 22 mW at the sample. The scattered light was directed through a polarizer in the analyzer, where it traveled through a 150 μm aperture and then into a holographic notch and supernotch filter (Kaiser Optical Systems). The spectrometer used a 1200 gr / mm diffraction grating (Richardson Grating Laboratory). The entrance slit of the JY-Horiba HR460 spectrometer was set at 6 cm. -1 Set the resolution to 50~1600cm -1 The spectrometer was frequency calibrated using CCl4 so that the recorded frequencies are within ±1 cm -1 Parallel polarization (VV) spectra were collected where the incident laser light was vertically polarized.

[0075] The assignments of the Raman vibrations are shown in Table 2. The assignments were based on the same method as Halasz et al. 19、20 The results are shown in Figure 1 for the supernatant and in Figure 2 for the precipitated solid. [Table 2]

[0076] FIG. 1 shows the Raman spectra of the supernatant samples of sodium silicate solution after mixing with barium chloride solution for 0.5 hours for four doses of barium chloride dehydrate. The spectrum of the activator solution without retarder (RM-BC-0) shows a Q 0 , Q 1 , and Q 2 This clearly shows that type Q silicate species dominates the surfactant solution. 0The type 1 silicate species are completely dissociated (Figure 1). All supernatants of samples containing barium chloride dihydrate (Table 1) are virtually free of silicate species, even at a very low dosage of Ba / Si molar ratio of 0.04 (RM-BC 0.875). This suggests that when the barium chloride solution was mixed with the alkaline sodium silicate activator solution, almost all of the silicates originally present in the activator solution were co-precipitated with barium hydroxide. Because silicate species precipitate as barium silicate complexes, the concentration of soluble silicate available for geopolymerization is very low during early setting. The limited availability of silicate species leads to delayed setting times by preventing the nucleation and growth of CSH and / CASH gels.

[0077] Figure 2 shows the Raman spectra of the co-precipitated solids after mixing the barium chloride solution with the activator solution for 0.5 h for three doses of retarder. The co-precipitated sample with the lowest dose of retarder (RM-BC 0.875) had a Q 0 , Q 1 and Q 2 In addition to the bands related to silicate species of type 1, 1062 cm -1 The Raman spectrum shows a sharp pattern with a new vibration band at 1062 cm -1 The band is Q 3 Comparing this Raman spectrum with the spectrum of the activator solution without retarder ( FIG. 1 , RM-BC00), in the disclosed embodiment, the addition of retarder leads to the formation of fully dissociated silicate species (Q 0 ) and other types of silicate species are found to decrease. Apparently, the barium cations interact to some extent with the silicate species, resulting in increased polymerization of the silicate species.

[0078] With increasing retarder dosage, the intensity of each Raman band decreased. When the retarder was increased to 5% BWOB or a B / Si molar ratio of 0.23 (Figure 2), the respective Raman bands almost completely disappeared, indicating that significant interactions between barium and silicate species were induced in the precipitated complex. The increased interactions at higher doses of barium chloride dihydrate significantly delayed the release of silicate species, thus significantly extending the curing time and producing a cured geopolymer with reduced early strength during that time.

[0079] example Examples of the subject matter The following examples illustrate the practice of the present disclosure in its preferred embodiments.

[0080] The following raw materials were used to prepare the samples in Examples 1-21. Two fly ashes were used. One was a high CaO FFA (12.5%) from Jewett Power Station, Texas, USA, sold by Headwater Resources (Jewett fly ash). This fly ash contains 12.2 wt% CaO and has a loss on ignition (LOI) of 0.15%. The sum of Si+Al+Fe oxides was 79.57 wt%, exceeding the minimum requirement of 75 wt% for Class F fly ash according to ASTM C618. The second fly ash was a low Ca FFA from Neilsens Group, Australia. This FFA was a product of a coarser fly ash classification. Its LOI was less than 0.15%. The sum of Si+Al+Fe oxides was about 93 wt%. Ground granulated blast furnace slag grade 120 (NewCem slag cement) was obtained from Lafarge-Holcim's Sparrow Point plant in Baltimore, Maryland. According to ASTM C989, the activity index was about 129. The blast furnace slag contained about 38.5% CaO, 38.2% SiO2, 10.3% Al2O3, and 9.2% MgO with an average particle size of 13.8 μm, with 50% by volume less than 7 μm. Metakaolin (Kaorock) was obtained from Thiele Kaolin Company, Sandersville, Georgia. The metakaolin particle size ranged from 0.5 to 50 μm, with 50% by volume less than 4 μm. Silica fume, an industrial waste product from Fe-Si alloys, was obtained from Norchem Inc. The silica fume contained 2.42% by weight carbon. Silica fume was used to prepare activator solutions by dissolving silica fume in alkali hydroxide solutions or was added as a submicron reactive filler in the preparation of ultra-high performance concrete samples.

[0081] Bluestone #7 (AASHTO T-27) was used as the coarse aggregate. To achieve saturated surface dry (SSD) conditions, the dry aggregate was soaked in water for 24 hours and then free water was manually removed from the aggregate surface using a dry cloth. River sand in SSD or oven-dried condition was used. Moisture content of fine aggregate samples was measured using a Trident solid moisture meter (Model T90). Min U-SIL® ground quartz powder from USSilica was used to prepare the ultra-high performance concrete. The particle size of the quartz powder ranged from 1 to 25 μm with a median particle size of approximately 5 μm.

[0082] An alkaline silicate activator solution was prepared using type Ru sodium silicate solution from PQ, Corp. The mass ratio of SiO2 / Na2O was about 2.40. The resulting solution contains about 13.9 wt% Na2O, 33.2 wt% SiO2, and 52.9 wt% water. Sodium hydroxide beads (99% purity) and potassium hydroxide flakes (91% purity) were used to prepare the alkaline activator solution.

[0083] Example 1 to Example 7 Geopolymer samples were prepared containing high Ca class F fly ash from Jewett Power Station, Texas, USA. The mix composition is shown in Table 3 with the ingredients in grams. The batch size was about 5000 grams. The Jewett fly ash contained about 12.2 wt% CaO. Geopolymer samples from Example 1 and Example 2 were prepared with retarder sodium hexametaphosphate (SHMP) for comparison. Sodium phosphate was disclosed as a retarder in the prior art or literature. The dosage of SHMP was 1.50% and 2.25% BWOB, respectively. For geopolymer samples from Example #4 to Example #7, they were prepared with retarder barium chloride dihydrate at dosages of 0.50% to 1.00 wt% BWOB to demonstrate the retardation efficiency.

[0084] The activator solution was prepared by dissolving NaOH beads (99% purity) in water and then combining the resulting solution with type Ru sodium silicate solution. Barium chloride dihydrate or sodium metaphosphate (SHMP) was separately dissolved in water to prepare the retarder solution. The retarder solution was mixed for 2 hours and then poured into Jewett fly ash in a high-intensity K-Lab mixer (Kercher Industries) for 6 minutes. The resulting fresh paste was immediately transferred to a mold (3 inches high and 40 mm high) and treated on a vibrating table for about 1 minute to remove trapped air bubbles. The initial and final set times were determined for the fresh paste using a Vicatronic Automatic Vicat machine (model E004N). Hereafter, the machine is referred to as AutoVicat according to ASTM C191. [Table 3]

[0085] The initial set time for the control sample (Example 3, BC00) was determined to be 29 minutes and the final set time was 45 minutes. Addition of barium chloride dihydrate at 0.50% BWOB increased the initial set time to 47 minutes and the final set time to 78 minutes (Example 4). Increasing the barium chloride dihydrate to 0.75% BWOB increased the initial set time to 68 minutes and the final set time to 99 minutes (Example 5). Increasing the barium chloride dihydrate to 0.875% BWOB increased the initial set time to 114 minutes and the final set time to 144 minutes (Example 6). Further increasing the barium chloride dihydrate to 1% BWOB increased the initial set time to 391 minutes and the final set time to 450 minutes (Example 7). Isothermal calorimetry data revealed that the addition of the retarder significantly reduced the heat of hydration of the geopolymer.

[0086] In comparison, doping with sodium metaphosphate at 1.5% BWOB gave an initial set time of 35 minutes and a final set time of 57 minutes. Increasing the sodium metaphosphate to 2.25% BWOB showed a slight increase in initial set time to 38 minutes and final set time to 63 minutes. Clearly, the present retarder is much more efficient than those disclosed in the prior art or literature.

[0087] Examples 8-10 Binary FFA / BFS geopolymer mortar samples are prepared with the mix composition shown in Table 4. The ingredients are given in grams. Low Ca class F fly ash from Neilsens Concrete, Australia, ground granulated blast furnace slag from Lafarge-Holcim, and river sand (saturated surface dry) were mixed in a Waring 7 quart planetary mixer for 3 minutes. An activator solution was prepared by dissolving NaOH beads in water and then combining the resulting solution with sodium silicate solution of type Ru. The activator solution was left overnight before use. Barium chloride dihydrate, if present, was dissolved in water separately. The retarder dosage was fixed at 0.875% BWOB.

[0088] Activator solution without barium chloride dihydrate (Example #8) was poured into the FFA / BFS / sand mix and mixed at medium speed for 5 minutes. The fresh mortar was measured for set time using an AutoVicat per ASTM C191. The initial set time was 114 minutes and the final set time was 186 minutes.

[0089] After mixing the retarder solution with the activator solution for 30 minutes, geopolymer mortar samples were prepared (Example 9). The setting time of the fresh mortar was measured by AutoVicat according to ASTM C191. The initial setting time was 249 minutes and the final setting time was 348 minutes.

[0090] The retarder solution was added when the activator solution was poured into the dry component mixture (Example 10). The mixture was mixed for 5 minutes. The fresh mortar was measured for set time using an AutoVicat according to ASTM C191. The initial set time was 236 minutes and the final set time was 342 minutes. [Table 4]

[0091] Examples 11-13 Binary FFA / BFS geopolymer mortar samples with the same mix composition as used in Examples 8-10 are prepared (Table 4). Low Ca class F fly ash from Neilsens Group, Australia, ground granulated blast furnace slag from Wagners, Australia, and river sand (saturated surface dry) were mixed in a Waring 7 quart planetary mixer for 3 minutes. An activator solution was prepared by dissolving NaOH beads in water and then combining the resulting solution with sodium silicate solution of type Ru. The activator solution was left overnight before use. Barium chloride dihydrate, if present, was dissolved in water separately. The retarder dosage was fixed at 1.25% BWOB.

[0092] Activator solution without barium chloride dihydrate (Example #11) was poured into the FFA / BFS / sand mix and mixed at medium speed for 5 minutes. The fresh mortar was measured for set time using an AutoVicat per ASTM C191. The initial set time was 59 minutes and the final set time was 144 minutes. The compressive strength was 4081 psi after 7 days of curing and increased to 8032 psi after 28 days of curing.

[0093] Geopolymer mortar samples were prepared after mixing the retarder solution with the activator solution for 30 minutes (Example 12). Set time was measured for fresh mortar with AutoVicat according to ASTM C191. Initial set time was 136 minutes and final set time was 198 minutes. Compressive strength was 3673 psi after 7 days of curing and increased to 7734 psi after 28 days of curing.

[0094] The retarder solution was added when the activator solution was poured into the dry component mixture (Example 13). The mixture was mixed for 5 minutes. The fresh mortar was measured for set time using an AutoVicat according to ASTM C191. The initial set time was 114 minutes and the final set time was 180 minutes. The compressive strength was 4064 psi after 7 days of curing and increased to 7970 psi after 28 days of curing.

[0095] Examples 14-16 To prepare the geopolymeric ultra-high performance concrete (GUHPC), metakaolin (5.71 wt%) and ground granulated blast furnace slag (14.72 wt%) were mixed in a high intensity mixer (K-Lab, Kercher Industries). The activator was prepared by mixing Na2O (2.12 wt%) as NaOH, K2O (1.35 qt% wt%) as KOH, SiO2 (3.95 wt%) as type Ru sodium silicate solution, and water (10.15 wt%). Barium chloride dihydrate, if present, was dissolved separately in water and combined with the activator solution 5 min before preparing the samples. The activator solution was then poured into the MK / BFS blend and mixed for 3 min at approximately 350 rpm. Dry river sand (50 wt%) and quartz powder (10.00 wt%) were then added to the mix and mixing was continued for 3 min. Towards the end of mixing, silica fume (2.00%) was added and mixing was continued for 3 min. The resulting pastes were subjected to initial setting times determined using either an AutoVicat or a manual Vicat machine. The pastes were poured into 2"x4" cylindrical molds and allowed to set at room temperature. Compressive strength was measured after 28 days of curing on a Test Mark CM-4000-SD compactor. The compactor was calibrated to NIST traceable standards.

[0096] In the absence of barium chloride dihydrate (Example 14), the initial set time was estimated to be about 30 minutes and the compressive strength after 28 days of cure was about 19,972 psi. With the addition of 1 wt. % BWOB barium chloride dihydrate (Example 15), the initial set time was 54 minutes and the compressive strength after 28 days of cure was about 20,146 psi. With the addition of 2 wt. % BWOB barium chloride dihydrate (Example 16), the initial set time increased to 89 minutes and the compressive strength after 28 days of cure was about 19,424 psi.

[0097] Examples 17-18 To prepare the GUHPC samples, metakaolin (5.92 wt%) and ground granulated blast furnace slag (15.28 wt%) were mixed in a high intensity mixer (K-Lab, Kercher Industries). The activator was prepared by mixing Na2O (1.08 wt%) as NaOH, K2O (2.47 wt%) as KOH, SiO2 (3.80 wt%) as silica fume, and water (9.45 wt%). Silica fume was dissolved in an alkali hydroxide solution and the resulting activator solution was aged for one week before use. Barium chloride dihydrate, if present, was dissolved separately in water and then combined with the activator solution 10 min before preparing the samples. The activator solution was then poured into the MK / BFS blend and mixed for 3 min at approximately 350 rpm. Dry river sand (50 wt%) and quartz powder (10.00 wt%) were then added to the mixture and mixing was continued for 3 min. Towards the end of mixing, silica fume (2.00%) was added and mixing continued for 3 minutes. The resulting pastes were subjected to initial and final set times using a manual Vicat machine. The pastes were poured into 2"x4" cylindrical molds and allowed to set at room temperature. Compressive strength was measured after 28 days of curing.

[0098] Without barium chloride dihydrate (Example 17), the initial set time was 15 minutes, the final set time was 19 minutes, and the compressive strength after 28 days of cure was about 26,418 psi. With the addition of 1.5 wt. % BWOB barium chloride dihydrate (Example 18), the initial set time was 73 minutes, the final set time was 81 minutes, and the compressive strength after 28 days of cure was about 23,817 psi.

[0099] Examples 19-20 Examples 19 and 20 demonstrate the efficiency of using soluble barium salts in controlling hardening of geopolymer concrete.

[0100] The mix composition for both concrete samples contained 78.75 wt% aggregate with a coarse to fine aggregate mass ratio of 1.74. The binder contained 80% low-CaO FFA and 20% blast furnace slag. The w / b ratio was 0.47, the NaOH molar concentration was 5.7, and the SiO2 / Na2O mass ratio was 1.15 for the activator solution. To prepare the geopolymer concrete samples, low-CaO FFA from Neilsens Group, Australia, blast furnace slag from Lafarge-Holcim, and river sand (SSD condition) were mixed in a high intensity mixer (K-Lab, Kercher Industries) for 3 minutes. The activator solution was prepared by dissolving NaOH beads in water and then combining the resulting solution with a sodium silicate solution of type Ru. The activator solution was left overnight before use.

[0101] The activator solution without retarder (example #19) was poured into the FFA / BFS / sand mix and mixed at 300 rpm for 3 minutes. SSD coarse aggregate (grade #7) was then added and mixed at a slow mixing speed (example 20 rpm) for 5 minutes. The fresh concrete was sieved to obtain mortar samples that were measured with an Acme Penetrometer per ASTM C403 for set time. The fresh concrete was also poured into a 3"x6" cylindrical mold and vibrated on a vibrating table for 1 minute. The samples were covered and allowed to cure at room temperature until compressive strength was measured. The initial set time was 75 minutes and the final set time was 168 minutes. The compressive strength after 7 days of cure was 4509 psi, increasing to 7992 psi after 28 days of cure.

[0102] Additional concrete samples with retarder were prepared using the same procedure described in Example 19 (Example 20). Barium chloride dihydrate was dissolved in water separately. The retarder dosage was 1.00% BWOB. The retarder solution was mixed with the activator solution for 30 minutes before preparing the fresh concrete samples. The fresh concrete was sieved and mortar samples were obtained for set time using Acme Penetrometer according to ASTM C403. The initial set time was 313 minutes and the final set time was 572 minutes. The compressive strength was 3707 psi after 7 days of curing and 7259 psi after 28 days of curing.

[0103] Example 21 The same mix composition as in Example #8 without the retarder solution was mixed for 30 minutes, then the retarder solution (3% Barium Chloride BWOB) was poured into the paste while mixing and mixed for another 10 minutes. After mixing was stopped, the mortar samples were subjected to ASTM C191 for setting time determination. At about 7.4 hours after pouring the activator solution into the dry mix, the mortar samples did not show any signs of setting, indicating that the retarder effectively delayed the setting. The retarder can be used for emergency setting brake of raw geopolymer concrete during transportation in a ready-mix truck.

[0104] While many embodiments of the present disclosure have been described in detail, it will be apparent that modifications and variations are possible without departing from the scope of the invention as defined in the appended claims. Moreover, it should be understood that all examples in the present disclosure, while illustrating many embodiments of the invention, are provided as non-limiting examples and therefore should not be construed as limiting the various implementations so illustrated.

[0105] References The following references are mentioned above and are incorporated herein by reference. 1. D. M. Roy, G. M. Dorr, "Hydration, Structure, and Properties of Blast Furnace Slag Cements, Mortars, and Concrete," ACI Materials Journal 79 (1982) pp. 444-457. 2. S. D. Wang, X. C. Pu, K. L. Scrivener, and P. L. Pratt, "Alkali-activated Slag Cement and Concrete: A Review of Properties and Problems," Advances in Cement Research 27 (1995) pp. 93-102. 3. JL Provis, JSJ van Deventer, Alkali Activated Materials, Springer:Houten, The Netherlands, 2014. 4. E.I. Diaz, E.N. Allouche, S. Eklund, "Factors Affecting the Suitability of Fly Ash as Source Material for Geopolymers", Fuel 89 (2010) pp. 992-999. 5. E. I. Diaz-Loya, E. N. Allouche, and S. Vaidya, "Mechanical Properties of Fly-Ash-Based Geopolymer Concrete", ACI Materials Journal 108 (2011) pp. 300-306. 6. P. Topark-Ngarm, P. Chindaprasirt, and V. Sata, “Setting Time, “Strength, and Bond of High-Calcium Fly Ash Geopolymer Concrete”, Journal of Materials in Civil Engineering 27 (2015). 7. L. Kalina, V. Bilek Jr., R. Novotny, M. Moncekova, J. Masilko and J. Koplik, "Effect of Na3PO4 on the Hydration Process of Alkali-Activated Blast Furnace Slag", Materials 9 (2016) pp. 395-403. 8. J. J. Chang, "A Study on the Setting Characteristics of Sodium Silicate-activated Slag Pastes", Cement and Concrete Research 33 (2003) pp. 1005-1011. 9. J. J. Chang, W. C. Y. Eih, C. C. Hung, "Effects of Gypsum and Phosphoric Acid on the Properties of Sodium Silicate-based Alkali-activated Slag Pastes," Cement and Concrete Composites 27 (2005) pp. 85-91. 10. C. Wu, Y. Zhang, Z. Hu, "Properties and Application of Alkali-slag Cement", Journal of the Chinese Ceramic Society 21 (1993) pp. 175-181. 11. U.Rattanasak, K.Pankhet, P.Chindaprasirt, "Effect of Chemical Admixtures on Properties of High-calcium Fly Ash Geopolymer", International Journal of Minerals Metallurgy and Materials, 18 (2011), pp. 364-369. 12. A.R. Brough, M. Holloway, J. Sykes, A. Atkinson, "Sodium silicate-based alkali-activated slag mortars: Part II. The retarding effect of additions of sodium chloride or malic acid", Cement and Concrete Research 30 (2000) pp. 1375-1379. 13. A. R. Sakulich, E. Anderson, C. Schauer, M. W. Barsoum, "Mechanical and Microstructural Characterization of an Alkali-activated Slag / Limestone Fine Aggregate Concrete", Construction and Building Materials 23 (2009) pp. 2951-2957. 14. C. L. Nicholson, B. J. Murray, R. A. F. Letcher, D. Brew, K. J. Mackenzie, M. Schmucker. Novel Geopolymer Materials Containing Borate Structural Units. In Proceedings of the World Congress Geopolymer, Perth, Australia, September 2005; pp. 31-33. 15. M. Davraz, "The Effects of Boron Compounds on the Properties of Cementitious Composites," Science and Engineering of Composite Materials 17 (2010) pp. 1-18. 16. G. R. Qian, D. D. Sun, J. H. Tay, "Characterization of mercury-and zinc-doped alkali-activated slag matrix Part II. Zinc," Cement and Concrete Research 33 (2003) pp. 1257-1262. 17. GR Qian, DD Sun, JH Tay, "Immobilization of Mercury and Zinc in an Alkali-activated Slag Matrix", Journal of Hazardous Materials B101 (2003) 65-77. 18. W. L. Gong, H. Xu, W. Lutze, and I. L. Pegg, Pumpable Geopolymer Compositions for Well Sealing Applications, U.S. Patent Application 15 / 597,227, filed May 17, 2017, pending (2016). 19. I. Halasz, M. Agarwal, R. B. Li, N. Miller, “What Can Vibrational Spectroscopy Tell about the Structure of Dissolved Sodium Silicates?” Microporous and Mesoporous Materials 135 (2010) pp. 74-81. 20. I. Halasz, M. Agarwal, R. B. Li, N. Miller, "Vibrational Spectra and Dissociation of Aqueous Na2SiO3 Solutions", Catalysis Letters 117 (2007) pp. 34-42.

[0106] All documents, patents, journal articles and other materials cited in this application are hereby incorporated by reference.

[0107] Although the present disclosure has been disclosed with reference to certain specific embodiments, numerous modifications, variations, and variations to the described embodiments are possible without departing from the scope and scope of the present disclosure, as defined in the appended claims. Accordingly, it is intended that the present disclosure not be limited to the described embodiments, but rather have its full scope defined by the language of the following claims and their equivalents.

Claims

1. at least one reactive aluminosilicate, a retarder-containing solution, and At least one alkali silicate activator solution A geopolymer composition having a controllable hardening time comprising: the at least one reactive aluminosilicate comprises low Ca class F fly ash (FFA) and blast furnace slag (BFS); The retarder is barium chloride dihydrate, The amount of barium chloride dihydrate is 0.5-5% BWOB; Geopolymer composition.

2. 2. The geopolymer composition of claim 1, wherein the low Ca class F fly ash (FFA) is a fly ash containing 8% by weight or less of calcium oxide.

3. 3. The geopolymer composition of claim 2, wherein the fly ash comprises at least 65% by weight of an amorphous aluminosilicate phase.

4. 3. The geopolymer composition of claim 2, wherein the fly ash has an average particle diameter of one of 60 μm or less, 50 μm or less, 45 μm or less, and 30 μm or less.

5. 2. The geopolymer composition of claim 1, wherein the low Ca class F fly ash (FFA) has a loss on ignition (LOI) of 5% or less.

6. 2. The geopolymer composition of claim 1, wherein the at least one reactive aluminosilicate further comprises metakaolin (MK).

7. 2. The geopolymer composition of claim 1, wherein the at least one reactive aluminosilicate comprises Class C fly ash (CFA) and metakaolin (MK).

8. 2. The geopolymer composition of claim 1, wherein the alkali silicate activator solution comprises a metal hydroxide and a metal silicate, and the metal of the metal hydroxide and the metal silicate is potassium, sodium or a combination of both.

9. 10. The geopolymer composition of claim 1, further comprising at least one aggregate.

10. 2. The geopolymer composition of claim 1, further comprising at least one micron or submicron filler.

11. 2. The geopolymer composition of claim 1, wherein the initial curing time is from 25 minutes to 24 hours.

12. 2. The geopolymer composition of claim 1, wherein the initial curing time is from 45 minutes to 180 minutes.

13. 2. The geopolymer composition of claim 1, wherein the initial curing time is from 90 minutes to 360 minutes.

Citation Information

Patent Citations

  • Alkali-slag cement component and preparation process thereof

    CN101723607A

  • Geopolymer cement and its use

    JP2013502367A

  • Ultra-high performance geopolymer composite for concrete

    JP2013545714A

  • Controlling the cure time of geopolymer compositions containing high CA reactive aluminosilicate materials

    JP2021506708A

  • Inorganic matrix compositions, composites incorporating the matrix, and process of making the same

    US20040182285A1